2020
DOI: 10.1038/s41386-020-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Δ9-Tetrahydrocannabinol (THC) impairs visual working memory performance: a randomized crossover trial

Abstract: With the increasing prevalence of legal cannabis use and availability, there is an urgent need to identify cognitive impairments related to its use. It is widely believed that cannabis, or its main psychoactive component Δ 9 -tetrahydrocannabinol (THC), impairs working memory, i.e., the ability to temporarily hold information in mind. However, our review of the literature yielded surprisingly little empirical support for an effect of THC or cannabis on working memory. We thus conducted a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…Indeed, in some cases, we even found distractor presence benefits whereby participants found the target faster when a salient singleton distractor was present. Because of the fairly large number of trials per participant that we collected (e.g., 1600 in Experiment 1) we anticipate this dataset will be useful for modeling the effects of stimulus history and non-target homogeneity (Calder-Travis & Ma, 2020;Mihali & Ma, 2020;Rosenholtz, 2001;Tseng et al, 2014) as well as for sub-sampling analyses to estimate the effect of trial counts on expected power for new within-and between-subjects task variants (Adam et al, 2020;Baker et al, 2020;Ngiam et al, 2021;Xu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in some cases, we even found distractor presence benefits whereby participants found the target faster when a salient singleton distractor was present. Because of the fairly large number of trials per participant that we collected (e.g., 1600 in Experiment 1) we anticipate this dataset will be useful for modeling the effects of stimulus history and non-target homogeneity (Calder-Travis & Ma, 2020;Mihali & Ma, 2020;Rosenholtz, 2001;Tseng et al, 2014) as well as for sub-sampling analyses to estimate the effect of trial counts on expected power for new within-and between-subjects task variants (Adam et al, 2020;Baker et al, 2020;Ngiam et al, 2021;Xu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians may feel comfortable with tailoring the medical cannabis treatment regimen knowing that patients are not at a significant overdose death risk. However, cannabis-associated health risks including Cannabis Use Disorder and complications resulting from the psychoactive effects of THC need to be considered, even at low doses (Adam et al 2020). This concept is important for the operation of motor vehicles, as well as occupational and recreational hazardous activity.…”
Section: Medical Cannabis Safety Considerationsmentioning
confidence: 99%
“…Reconciliation of these contradictory findings is challenging considering the heterogeneity in the tasks used. A detailed analysis of 15 published studies assessing the dose effects of 9 -THC on digitspan performance, demonstrated that negative results may be due to short task length (and low number of trials, e.g., 3min Digit Span task), which imparts lower sensitivity to detect an effect compared to longer task durations (39). Altogether, there is converging evidence that the cannabis impairing effects on verbal learning and memory, response inhibition, and psychomotor speed occur in a dose-response fashion.…”
Section: -Thc Contentmentioning
confidence: 99%
“…Specifically for attention and working memory domains, the literature reports mixed findings: while most studies observed that the severity of impairments are a function of Δ 9 -THC content or performance is solely affected by the higher dose ( 30 32 , 34 , 35 , 38 , 39 ), some found that these domains were unaffected by Δ 9 -THC ( 32 , 34 , 36 ). Reconciliation of these contradictory findings is challenging considering the heterogeneity in the tasks used.…”
Section: Acute Effectsmentioning
confidence: 99%